Induction of adaptive immune response by self-aggregating peptides - Jesus Zepeda-Cervantes; Luis Vaca (Taylor & Francis Group, 2018)
Introduction: Recently, subunit vaccines are replacing some of the traditional vaccines because they offer a higher margin of safety. However, generally subunit vaccines have low antigenicity. Adjuvants are used in vaccine formulations to increase their immunogenicity, but current research suggests that adjuvants could induce serious side effects in susceptible individuals; therefore, the improvement of antigens and adjuvants is important. Areas covered: Here we reviewed some self-aggregating peptides (SAPs) used as antigen delivery systems. SAPs are based on a short sequence of amino acids, which have self-aggregating properties, inducing self-interaction among peptide molecules by means of non-covalent interactions to generate nanoparticles (NPs). Expert commentary: SAPs increase the immunogenicity of fused/conjugated antigens because they can interact with antigen-presenting cells and induce adaptive immunity based on both humoral and cellular responses. As an example, we report an antigen delivery system based on SAPs forming NPs. These NPs are synthesized using a recombinant baculovirus. We fused the green fluorescent protein to the first 110 amino acids of polyhedrin protein from Autographa californica nucleopolyhedrovirus, which has self-aggregating properties. We showed that these NPs prompt high antibody levels without inducing inflammation, similarly to some SAPs reported here.